Черный соболь, Недопесок и другие...: [для младшего и среднего школьного возраста] - Д. Н. Мамин-Сибиряк (Репро, 2019)
Экземпляры: БС (20200122) / Инвентарный номер: РТШ54872 / Цена: / Сис.шифр: 84(2) / Авт.знак: Ч-49 / ГРНТИ: 17.82.82 / ББК: 84(2=411.2)-4я43